Pengembangan Media Pembelajaran Padlet Berbasis Model Project Based Learning dan Profil Keterampilan Menulis Cerita Siswa Kelas VI Sekolah Dasar - Indah Purnama Sari; Abdul Muktadir; Gumono (Jurnal Kajian Pendidikan Dasar, 2026)
This study aims to: (1). Describe the characteristics of the Padlet learning media. (2). Analyze the feasibility of the Padlet learning media. (3). Describe the responses of students and teachers to the Padlet learning media. (4). Map the profile of the story writing ability of sixth grade elementary school students in the development of the Padlet learning media. The results of the study show (1) that the Padlet learning media based on the Project Based Learning model was developed using the type of research and development or Research and Development (R&D) with the ADDIE model: Analysis (analysis), Design (design), Development (development), Implementation (implementation), and Evaluation (evaluation). The resulting product is the Padlet learning media based on the Project Based Learning model which encourages the writing ability of sixth grade elementary school students. (2) Suitability of Padlet Media as Learning Media. The validation results from material experts, media experts, and learning practitioners show that the developed Padlet media is included in the "very suitable" category for use in learning to write stories. (3) Teacher and student responses to the Padlet learning media with very good criteria and student responses with very interesting criteria. The teacher assessed that the product was very good to use, helped the learning process, and was in accordance with the demands of the Independent Curriculum. Students showed high enthusiasm, felt interested in participating in the learning process so that this media could be used and applied in the field. (4) The profile of students' story writing abilities using Padlet learning media based on the Project Based Learning model showed a very good profile of students' story writing abilities.